Pengenalan Dan Pelatihan Sitasi Karya Ilmiah Menggunakan Aplikasi Mendeley - Octariani Pramiastuti; Desi Sri Rejeki; Anggit Pratiwi (JABI: Jurnal Abdimas Bhakti Indonesia, 2020)
Citation is a crucial element for making a scientific paper. in general, novice writers do plagiarism accidentally. The existence of software that can be used to help writing citations, allowing writers to process reference documents they have, and making groupings based on specific topics/categories. The citation cannot be separated from a scientific paper. Citation becomes very important in writing like scientific papers. Usually, the writers of scientific papers get caught in a mistake because they are not careful in writing a citation. Mendeley is a software that has an Open Source concept and can be used freely by lecturers, researchers, and students to process and organize scientific documents and references. The knowledge of students of the Pharmacy Study Program of STIKes Bhamada Slawi about research citations or scientific works is still limited to manuals for practicum subjects, independent assignments, group assignments, or thesis courses. In making citation, it is necessary to pay attention to the procedure, for example the name of the journal which must be abbreviated or written in full. The target activities of this community service are Pharmacy S1 Study Program. The results of this activity are adding new insights for participants in making scientific writings as well as making it easier to search written literature. It is also hoped that the participants will be able to manage scientific references by utilizing Mendeley so that they will improve the quality and dissemination of research from lecturers, researchers, and students of STIKes Bhakti Mandala Husada Slawi.